A Young Woman With Recurrent Gestational Hypercalcemia and Acute Pancreatitis Caused by CYP24A1 Deficiency. (6th May 2016) - Woods, Gina N; Saitman, Alec; Gao, Hanlin; Clarke, Nigel J; Fitzgerald, Robert L; Chi, Nai‐Wen
ABSTRACT: The CYP24A1 gene encodes a mitochondrial 24‐hydroxylase that inactivates 1, 25(OH)2 D. Loss‐of‐function mutations in CYP24A1 cause hypercalcemia, nephrolithiasis and nephrocalcinosis. We describe a woman with CYP24A1 deficiency and recurrent gestational hypercalcemia. Her first pregnancy, at age 20, resulted with the intrauterine demise of twin fetuses. Postpartum, she developed severe hypercalcemia (14 mg/dL), altered mental status, and acute pancreatitis. Her PTH was suppressed (6 pg/mL) and her 1, 25(OH)2 D was elevated (165 and 195 pg/mL on postpartum day 1 and 5, respectively). Between one and three months postpartum, her serum calcium decreased from 11.4 to 10.2 mg/dL while her 1, 25(OH)2 D level decreased from 83 to 24 pg/mL. Her 24‐hour urine calcium was 277 mg. Six months postpartum, she became pregnant again. At 14 weeks, her albumin‐corrected calcium level was 10.4 mg/dL and her 1, 25(OH)2 D level exceeded 200 pg/mL. To establish the diagnosis of CYP24A1 deficiency, we showed her 24, 25(OH)2 D level to be undetectable (<2 ng/mL). Exon sequencing of the CYP24A1 gene revealed a homozygous, 8‐nucleotide deletion in exon 8, causing an S334V substitution and premature termination due to a frame shift (c.999_1006del, p.Ser334Valfs*9). To prevent hypercalcemia, she was advised to discontinue prenatal vitamins, avoid sun exposure and calcium‐rich foods, and start omeprazole and a calcium binder (250 mg K‐Phos‐neutral with meals). Despite these measures, both hypercalcemia (11.5 mg/dL) and acute pancreatitis recurred. Labor was induced and a healthy, normocalcemic boy was delivered. In the absence of lactation, maternal hypercalcemia resolved within 2 months. This report shows that CYP24A1‐deficient subjects may be normocalcemic at baseline. Hypercalcemia may be unmasked by pregnancy through the routine use of calciferol‐containing prenatal vitamins, increased 1‐alpha hydroxylation of VitD by the placenta and maternal kidney, and production of PTHrP by the uteroplacental unit. CYP24A1 deficiency should be considered in patients with unexplained vitamin D‐mediated hypercalcemia. © 2016 American Society for Bone and Mineral Research.